Bacterial Biofilm and Peculiarities of Its Formation in Plague Agent and in Other Pathogenic Yersinia - L. M. Kukleva; G. A. Eroshenko; N. A. Vidyaeva; V. V. Kutyrev (Проблемы особо опасных инфекций, 2011)
This paper represents a review of the current literature data concerning general principles of bacterial biofilm formation, stages of biofilm production and its structural and functional organization, as well as the data concerning involvement of different enzyme systems with the process of biofilm functioning. Carried out is the analysis of the data on the peculiarities of biofilm formation by pathogenic Y. pestis, Y. pseudotuberculosis, and Y. enterocolitica. Displayed are the data on the role of hmsHFRS-operon genes, located in pigmentation chromosomal region of Y. pestis, in the process of biofilm structure formation, and the data on its regulation by hmsP and hmsT genes. Summarized are the results of the recent years' investigations devoted to the genetic determinancy of the plague agent biofilm formation processes, and in particular to the involvement of genes encoding synthesis of lipopolysaccharide (waaA, yrbH and gmhA) and polyamines (speA and speC), as well as rcsA and phoP-phoQ regulatory genes with biofilm formation procedures. Represented are the results of our own investigations concerning the studies of peculiarities of biofilm formation by plague agent strains of different subspecies on the abiotic surfaces and on the nematode model - Caenorhabditis elegans. Discussed is the role of the biofilm in the complex life span of the plague agent. Noted is biofilm significance not only for facilitation in plague transmission by fleas, but also for Y. pestis preservation in the environment, out of the organism of a warm-blooded host.